Formation of Synodal Regime of Church Administration in Context of Relationship between Secular and Spiritual Authorities in 1721—1725 (Nizhny Novgorod Diocese) - A. V. Bodrin (Научный диалог)
The article is devoted to the formation of the synodal regime of government of the Russian Orthodox Church and related problems in the relationship between secular and spiritual authorities. Attention is paid to the new policy of the state represented by the Synod in relation to the local episcopate. The peculiarities of the organization of the diocesan administration are characterized on the materials of the Nizhny Novgorod region. A brief biography of the local Bishop Pitirim, one of the close associates of Peter I is presented. The results of the analysis of problems in relations between the state and the church in the political sphere are given. A classification of these problems is proposed on the basis of various aspects of interaction between secular and clergy. Special attention is paid to issues related to the status of the Synod and its real possibilities to represent the interests of the clergy. It is shown on regional material that the clergy, under synodal conditions, found themselves in a dependent position on the authorities, both central and local. The author especially dwells on the facts describing the arbitrariness of officials in relation to persons of clergy, interference in their competence on certain issues. It has been proved that the establishment of the Synod and the general bureaucratization during the reign of Peter I changed the nature of church-state relations and acted as prerequisites for the emergence of new difficulties.